IMPLEMENTASI KEBIJAKAN PERLINDUNGAN HUTAN DI TAMAN NASIONAL (Studi Kasus Resort Wilayah Srumbung Balai Taman Nasional Gunung Merapi) - , DECKY HENDRA PRASETYA; , Dr. Nunuk Dwi Retnandari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Implementation of forest protection policy is expected to realize the sustainable of of Mount Merapi National Park (TNGM) forest so that it can be used optimally due to its function. However, it is still found ruined forest of TNGM caused human activities such as forest encroachment for agricultural land and illegal mining. This paper aims to assess the implementation of the policy on the protection of forests in national parks, case study at Srumbung Region Resort, TNGM. The study use qualitative method. Collecting data include objects related to forest protection policies are obtained from the observation, in-depth interviews and document research. The results of the study presented in the form of a description of information on the implementation of forest protection policies in Srumbung Region Resort, TNGM and its problems also the factors. The results of the study indicate that forest protection policies have been implemented in Srumbung Region Resort , TNGM through preemptive measures, preventive and repressive, but not yet fully succeeded in realizing the goal of appropriate policy intent. Some problems found in the implementation of forest protection policies in Srumbung Region Resort, TNGM a high dependence of community to forest area and forest resources, support from stakeholders are still weak, the presence of key figures in the community who have not been able to be controlled by implementing policies, as well as the abundance of availability sand in the forest area. The causing factors of these problems are the economic surrounding communities, the communication, capacity executing and implementing disposition or attitude.